Re-opening of banks' certificates of deposit market - Pertti Haaparanta; Tarja Heinonen (Bank of Finland, 1990)
The paper analyzes the applicability of variable parameter models to examine the behaviour of the interest rates in the market for cd's on the first market day after the bank strike, 7.3.1990, and on the first "normal" Wednesday after the strike, 21.3.1990. The data is minute data and variable parameter models are used as a way to capture the impact of information processing by traders on the interest rates. The results indicate that variable parameter models give satisfactory results. According to the models, the behaviour of the interest rates was more erratic before the interventions by the the Bank of Finland on both days. The banks' receive information on their position vis á vis the Bank of Finland at noon. On the 7.3. this information seemed to surprise banks whereas on the 21.3. there is no evidence of this.
URN:NBN:fi:bof-201908061350
Keywords: 330